2015
DOI: 10.15740/has/ajss/10.2/228-236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus, sulphur and biofertilizer on productivity and soil fertility after harvest of moongbean grown on light textured soil of Kachchh

Abstract: A field experiment consisted of 24 treatment combinations of three levels of phosphorus(0, 20, 40 kg ha-1) and three levels of sulphur (0, 20, 40 kg ha-1) and two level of biofertilizer in form of Rhizobium inoculation (inoculated and uninoculated) was conducted with four consecutive years from 2007-08 to 2010-11 were tested with three replications effect of under factorial Randomized Block Design at Bhachau-Kachchh to study the effect of P, S and Rhizobium on productivity and fertility of soil after harvest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…The increased in the parameters at 40 kg P 2 O 5 ha -1 might have been on account of stimulation of root growth of the crop as phosphorus plays an important role in various physiological process including root development, nodulation and N-fixation, better utilization of available growth resources viz., nutrient, moisture and solar radiation to a greater extent and accumulation of photosynthates. Similar results were also observed by Kadam and Khanvikar (2015), Sathyamoorthi et al (2008) and Sipai et al (2015).…”
Section: Effect Of Spacing and Levels Of Phosphorus On Growth Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…The increased in the parameters at 40 kg P 2 O 5 ha -1 might have been on account of stimulation of root growth of the crop as phosphorus plays an important role in various physiological process including root development, nodulation and N-fixation, better utilization of available growth resources viz., nutrient, moisture and solar radiation to a greater extent and accumulation of photosynthates. Similar results were also observed by Kadam and Khanvikar (2015), Sathyamoorthi et al (2008) and Sipai et al (2015).…”
Section: Effect Of Spacing and Levels Of Phosphorus On Growth Parameterssupporting
confidence: 89%
“…These altogether resulted in to overall increase in the above characters. Similar findings were also observed by Patel et al (2013) and Sipai et al (2015). Harvest index varied significantly due to spacing, where highest value (26.36 %) was recorded at 30 x 10 cm spacing which was at par with 20 x 10 cm spacing and the lowest value (25.21 %) was observed at 20 x 10 cm spacing.…”
Section: Effect Of Spacing and Levels Of Phosphorus On Yield And Yield Parameterssupporting
confidence: 88%
“…Data showed that the significantly higher NPK and S uptake of ~ 37, 4, 7, 1.26 kg ha -1 in seed and the uptake of in stover ~ 15, 3, 28, 1.57 kg ha -1 of NPK and S, respectively. It may be due to the effect of symbiotic rhizobacteria augment nodulation in root and increased N-fixation and improve the availability of N and others nutrient in soil (Sipai et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile in case of OC, available NP and S content increased (2, 4.5, 2 and 22%), respectively by application of 20 kg S as compared to control plot (Table 4). Available N and S content increased with increasing doses of S (Sipai et al, 2015). Bio-priming also influenced the available soil nutrients (Meena et al, 2016).…”
Section: Available Soil Nutrientsmentioning
confidence: 95%
See 1 more Smart Citation